Analysis on Corporate Governance Influences toward Banking Efficiency with Bank Category as Moderator Variable - Lidiyawati Lidiyawati (Binus Business Review, 2015)
Corporate governance system of Sharia financial institution that based on Islamic law may result more  variables principles then conventional owns. The restriction of usury are highly speculative transaction, embedded prohibited matter are main features in Sharia business institution. Sharia Supervisory Board, as board that supervises banking practices conforms to Sharia stipulations, hold strong important role within Islamic banking. Both important points above had direct effects on efficiency which attained by Islamic banking compared with conventional banking. This study examines the influence of corporate governance implementation toward efficiency banking sector with bank category as moderator variable. This study hypothesize that corporate governance has significant influences toward bank’s efficiencies, the influence of corporate governance toward Islamic bank efficiencies is higher than conventional bank, and level of Islamicbank efficiencies is higher than conventional bank. Measurement of efficiencies is using Stochastic Frontier Approach program, and then using SPSS in procces hypothetical model. The results of the study do not support the hypothesis. Examined result shows that statically corporate governance is not influenced by bank efficiency achievement. Corporate governance influences over Islamic bank has not show higher significance than conventional and Islamic bank efficiencies remain steady. Data limitations, complexity of the efficiency measures and the complexity of the operation of Islamic banks may explain the finding.